Evaluation of the Implementation of Article 21 and PP Number 58 of 2023’s Income Tax Calculation at PT. KC in Manado - Putong, Ivonne Helena; Ropa, Grace; Koagouw, Harty U.H.L.; Lasut, Jeane Christine (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Income Tax (PPh) Article 21 is the second largest contributor of tax types to state revenue. PPh Article 21 is not calculated and paid directly by the recipient of income but through a third party. This study aims to determine whether the calculation of PPh Article 21 at PT. KC is in accordance with tax laws and regulations. This is important so that no individuals involved is harmed. Data collection was carried out by interviewing, data documenting, and finding reports in the company and regulations related to PPh Article 21 that apply. The data collected was analyzed using qualitative methods and compared with the generally applicable Tax Regulations. The scope of the study was December 2023 - January 2024. The findings of this study are that the calculation of PPh Article 21 of the company in January - December 2023 contained an error in determining the amount of office costs. As a result, the PPh Article 21 that was deducted was greater than it should have been. In January 2024, the company has not implemented PP No. 58 of 2023. This PP is effective from January 1, 2024, but the company is still using the old laws in calculating employee Article 21 Income Tax.